Linkage analyses in Caribbean Hispanic families identify novel loci associated with familial late‐onset Alzheimer's disease. Issue 12 (30th September 2015) - Barral, Sandra; Cheng, Rong; Reitz, Christiane; Vardarajan, Badri; Lee, Joseph; Kunkle, Brian; Beecham, Gary; Cantwell, Laura S.; Pericak‐Vance, Margaret A.; Farrer, Lindsay A.; Haines, Jonathan L.; Goate, Alison M.; et al.
Abstract: Introduction: We performed linkage analyses in Caribbean Hispanic families with multiple late‐onset Alzheimer's disease (LOAD) cases to identify regions that may contain disease causative variants. Methods: We selected 67 LOAD families to perform genome‐wide linkage scan. Analysis of the linked regions was repeated using the entire sample of 282 families. Validated chromosomal regions were analyzed using joint linkage and association. Results: We identified 26 regions linked to LOAD (HLOD ≥3.6). We validated 13 of the regions (HLOD ≥2.5) using the entire family sample. The strongest signal was at 11q12.3 (rs2232932: HLOD max  = 4.7, P joint  = 6.6 × 10 −6 ), a locus located ∼2 Mb upstream of the membrane‐spanning 4A gene cluster. We additionally identified a locus at 7p14.3 (rs10255835: HLOD max  = 4.9, P joint  = 1.2 × 10 −5 ), a region harboring genes associated with the nervous system ( GARS, GHRHR, and NEUROD6 ). Discussion: Future sequencing efforts should focus on these regions because they may harbor familial LOAD causative mutations.